Phenols and GABAA receptors: from structure and molecular mechanisms action to neuropsychiatric sequelae - Menzikov, Sergey A.; Zaichenko, Danila M.; Moskovtsev, Aleksey A.; Morozov, Sergey G.; Kubatiev, Aslan A. (Frontiers in Pharmacology, 2024)
γ-Aminobutyric acid type A receptors (GABAARs) are members of the pentameric ligand-gated ion channel (pLGIC) family, which are widespread throughout the invertebrate and vertebrate central nervous system. GABAARs are engaged in short-term changes of the neuronal concentrations of chloride (Cl -) and bicarbonate (HCO3 -) ions by their passive permeability through the ion channel pore. GABAARs are regulated by various structurally diverse phenolic substances ranging from simple phenols to complex polyphenols. The wide chemical and structural variability of phenols suggest similar and different binding sites on GABAARs, allowing them to manifest themselves as activators, inhibitors, or allosteric ligands of GABAAR function. Interest in phenols is associated with their great potential for GABAAR modulation, but also with their subsequent negative or positive role in neurological and psychiatric disorders. This review focuses on the GABAergic deficit hypotheses during neurological and psychiatric disorders induced by various phenols. We summarize the structure-activity relationship of general phenol groups concerning their differential roles in the manifestation of neuropsychiatric symptoms. We describe and analyze the role of GABAAR subunits in manifesting various neuropathologies and the molecular mechanisms underlying their modulation by phenols. Finally, we discuss how phenol drugs can modulate GABAAR activity via desensitization and resensitization. We also demonstrate a novel pharmacological approach to treat neuropsychiatric disorders via regulation of receptor phosphorylation/dephosphorylation.